From Urban Strangers to Co-Producers of Grassroots Governance: A Theoretical Framework for the Civic Incorporation of Platform Workers in Urban China - Yiyue Yin (International Journal of Social Science and Public Policy, 2026)
This article addresses a central paradox of platform-mediated urban life in contemporary China: place-based platform workers—especially food delivery riders and couriers—are deeply embedded in the physical fabric of cities through their daily labor, yet remain only partially incorporated into the social relations and institutional mechanisms of urban governance. Drawing on recognition theory, social embeddedness, co-production of public services, and platform labor process theory, the article constructs a six-stage theoretical framework that traces the trajectory from “urban stranger” to “governance co-producer.” The framework develops a recursive theoretical process linking recognition, embeddedness, co-production, and deepened urban incorporation, and argues that civic incorporation and governance participation are mutually constitutive rather than simply sequential. The article also identifies structural constraints that risk reducing incorporation to instrumental co-optation, including algorithmic time poverty, moralized reciprocity, and uncompensated governance labor. The analysis contributes to urban governance theory by reconceptualizing platform workers as public actors whose mobile local knowledge represents a distinctive civic resource, while insisting that legitimate co-production requires substantive recognition of workers’ rights, temporal autonomy, and voice in rule-making.